Alcohol consumption and smoking history at the time of diagnosis and the risk of colorectal cancer recurrence and mortality: results from the ColoCare study - Loroña, Nicole C.; Himbert, Caroline; Ose, Jennifer; Cohen, Stacey A.; Strehli, Ildiko; Ulrich, Cornelia; Cobos, Sofia; Jean-Baptiste, Esther; Bloomer, Amanda M.; Figueiredo, Jane C.; Gigić, Biljana; Hardikar, Sheetal; et al. (Cancer epidemiology, biomarkers & prevention, 2025)
Background: Findings from studies investigating the impacts of alcohol use and smoking on colorectal cancer outcomes are inconclusive. This study aimed to investigate associations between alcohol use and smoking status at the time of diagnosis on recurrence and overall mortality among patients with colorectal cancer.Methods: The present study included 2,216 stage I-IV patients with colorectal cancer from the longitudinal multicenter ColoCare Study, with available data on recurrence and colorectal cancer-specific mortality. Cox proportional hazards models adjusted for age, sex, race, ethnicity, stage, tumor site, treatment, comorbidities, body mass index, and study site were fit, with imputations for missing data.Results: We observed 235 recurrences and 308 colorectal cancer-specific deaths over an average of 3 years of follow-up. After adjusting for confounders, current alcohol consumption and ever smoking, relative to not current consumption and never smoking, respectively, were not statistically significantly associated with colorectal cancer recurrence [alcohol-HR, 0.95. 95% confidence interval (CI), 0.71-1.29; ever smoking-HR, 0.98, 95% CI, 0.75-1.29] or colorectal cancer-specific mortality (alcohol-HR, 0.95. 95% CI, 0.74-1.22; ever smoking-HR, 0.98, 95% CI, 0.77-1.24).Conclusions: No associations were observed between alcohol and smoking at diagnosis and clinical outcomes in this well-annotated longitudinal cohort.Impact: Our cohort study reports no significant associations; however, limiting alcohol use and avoiding smoking are health behaviors recommended for colorectal cancer survivors for prevention of other cancers and chronic conditions.
Gesehen am 05.11.2025